Rh(III)‐Catalyzed Selective C7 Halogenation of Indolines. Issue 39 (19th October 2021) - Manisha,; Gupta, Shiv Shankar; Dhiman, Ankit Kumar; Sharma, Upendra
Abstract: An efficient Rh‐catalyzed catalytic method has been developed for selective C7 halogenation of N‐ pyrimidyl indolines with N ‐halosuccinimides (Cl, Br, I) to produce corresponding halides in good to excellent yields. The advantages of this strategy include broad substrate scope and excellent regioselectivity for C7 functionalization of indolines and feasibility at gram scale level. Various control experiments have been performed to understand the reaction pathway. Applicability of current methodology has been demonstrated by indole synthesis and post‐transformation of the C7 halogenated indolines into different valuable molecules. Abstract : N ‐pyrimidyl indolines were reacted with N ‐halosuccinimides to form C7‐halogenated indolines under rhodium‐catalysis with broad substrate scope. C7‐brominated product was also obtained in good yield at gram scale. Synthetic utility is demonstrated by indole synthesis followed by directing group removal and functional group transformation.